Pengembangan Android Apps Berbasis Discovery Learning Untuk Meningkatkan Pemahaman Konsep Matematis Siswa Kelas VII - Lilik Ariyanto; Derisna Aditya; Ida Dwijayanti (Edumatika : Jurnal Riset Pendidikan Matematika, 2019)
Lack of innovative learning media that is interesting, practical and easy to use in learning such as listening to lesson modules or seeing powerpoint shows used by teachers, thus causing learning to be ineffective, unattractive, and slow to understand, this results in a lack of understanding of mathematical concepts. Because of this, researchers are trying to develop an interesting and interactive learning media. This type of research is development research that aims to produce learning media on Android-based discovery learning apps that are feasible to use and to improve understanding of mathematical concepts of seventh-grade students. The method used is the ADDIE method. Which consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. Data analysis was carried out by normality, homogeneity, n-gain test, and right-sided t test. The results of this study can be concluded that (1) the results of the percentage of media expert validation amounted to 80.26%, material experts 86.36% and student response responses of 87.16% with the criteria of each very good. (2) the results of the n-gain test obtained that there is an increase in understanding of mathematical concepts of students who use learning media on Android-based discovery learning applications. (3) data from the field shows that student learning outcomes that obtain learning media android apps based on discovery learning are better than students who use conventional learning